Morphometric parameters of pelvic lymph nodes in experimental metastatic prostate cancer - V. V. Astashov; N. G. Kulchenko (Исследования и практика в медицине)
The study purpose. Identification of structural and functional changes in pelvic lymph nodes in experimental metastatic prostate cancer.Materials and methods. The study included 30 male mice aged 3 months. All animals (n = 30) were divided into 2 groups. The first group (the main one, n = 20) included mice that had a model of metastatic prostate cancer created by transplanting an Ehrlich tumor into the prostate parenchyma. These animals were further divided into two equal subgroups: 1a (n = 10) – mice were withdrawn from the experiment on day 7; 1b (n = 10) – mice were withdrawn from the experiment on day 18. The second group (n = 10) included mice that were not manipulated, they made up the control group. After the end of the experiment, morphological analysis of the prostate gland and regional (pelvic) lymph nodes in mice of both groups was performed using light microscopy. Statistical processing of the results was carried out using the Statistica 8.0 software package. The differences were considered statistically significant at p < 0.05.Results. When compared to the control group the mice of groups 1a and 1b, the prostate parenchyma was almost completely replaced by atypical cells, which demonstrates the presence of neoplastic processes in the prostate gland. In group 1a mice, the number of pelvic lymph nodes was 1.9 times as large, and in group 1b animals, this indicator was 2.7 times higher compared to the second group (p < 0.01). In animals of the first group, the proportion of mast cells in the pelvic lymph nodes increased by 121 % compared to the control group (p < 0.01). At the same time, we revealed a direct relationship of mast cells with the number of tumor cells and immunoblasts in the medullar sinuses, which indicates the participation of tissue basophils in tumor metastasis. We also recorded a significant increase in the area of the medullar sinuses of regional lymph nodes in animals of groups 1a by 12.4 % (p < 0.05) and 1b by 20.2 % (p < 0.01) against the background of an increase in the number of mast cells in this zone compared to the control group, which indicates the possible participation of mast cells in lymphangiogenesis.Conclusion. Mast cells can potentially play a role in the development of malignant neoplasms of the prostate gland. The number of mast cells increases in pelvic lymph nodes in animals with a created model of metastatic prostate cancer. The obtained direct dependence of the increase in the number of mast cells and the increase in the number of tumor cells with immunoblasts suggests the participation of tissue basophils in the spread of metastases. It can be assumed that infiltration of lymph nodes by mast cells may correlate with a poor prognosis of prostate cancer, since these granulocytes contribute to tumor metastasis.